The Effectiveness of a Multicenter Quality Improvement Collaborative in Reducing Inpatient Mortality. Issue 2 (June 2015) - Kroch, Eugene; Duan, Michael; Martin, John; Bankowitz, Richard; Kugel, Marla
Abstract : Motivation and Background: This study examines the evidence that a particular quality improvement collaborative that focused on Quality, Efficiency, Safety and Transparency (QUEST) was able to improve hospital performance. Setting: The collaborative included a range of improvement vehicles, such as sharing customized comparative reports, conducting online best practices forums, using 90-day rapid-cycle initiatives to test specific interventions, and conducting face-to-face meetings and quarterly one-on-one coaching sessions to elucidate opportunities. Methods: With these kinds of activities in mind, the objective was to test for the presence of an overall "QUEST effect" via statistical analysis of mortality results that spanned 6 years (2006-2011) for more than 600 acute care hospitals from the Premier alliance. Results: The existence of a QUEST effect was confirmed from complementary approaches that include comparison of matched samples (collaborative participants against controls) and multivariate analysis. Conclusion: The study concludes with a discussion of those methods that were plausible reasons for the successes.